2016
DOI: 10.2465/jmps.160719c
|View full text |Cite
|
Sign up to set email alerts
|

Pressure–volume–temperature equation of state of ε–FeOOH to 11 GPa and 700 K

Abstract: A new synchrotron X-ray diffraction study of ε-FeOOH has been carried out to determine the pressure-volumetemperature (P-V-T ) equation of state (EOS). The P-V-T data fitted a third-order Birch-Murnaghan EOS yielded: isothermal bulk modulus K T0 of 135(3) GPa; its pressure derivative K′ of 6.1(9); (∂K T /∂T ) P of −0.05(2) GPa K −1 ; a 0 of 2.6(7) × 10 −5 K −1 and a 1 of 1.0(3) × 10 −7 K −2 , where the volumetric thermal expansion coefficient is described as α 0,T = a 0 + a 1 × (T − 300).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
5
4
0
Order By: Relevance
“…To further examine the change of compression behavior, the variations in a/c and b/c are plotted in Figure 4. The ratios are similar to the values obtained by Suzuki (2010Suzuki ( , 2016 at each pressure except for b/c ratios at high pressure (5-10 GPa). The difference may have been caused by the deviatoric stress in the experimental cell under high pressure.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…To further examine the change of compression behavior, the variations in a/c and b/c are plotted in Figure 4. The ratios are similar to the values obtained by Suzuki (2010Suzuki ( , 2016 at each pressure except for b/c ratios at high pressure (5-10 GPa). The difference may have been caused by the deviatoric stress in the experimental cell under high pressure.…”
Section: Resultssupporting
confidence: 85%
“…In addition to the compressibility of other distorted rutile type M 3+ OOH (e.g., Ga, In, and CrOOH in Sano-Furukawa et al, 2012;MnOOH in Suzuki, 2013), the compressibility of ε-FeOOH displays an anisotropic behavior; the b axis is more compressible than the a and c axes. This combination of the directions of compressibility is consistent with the XRD studies of ε-FeOOH (Gleason et al, 2013;Suzuki, 2016), δ-AlOOH (Sano-Furukawa et al, 2009;Suzuki, 2009), GaOOH and InOOH (Sano-Furukawa et al, 2012). To further examine the change of compression behavior, the variations in a/c and b/c are plotted in Figure 4.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…After quenching to ambient conditions, the recovered samples were examined and confirmed on a diffractometer ( Figure 1). The lattice parameters and volume at ambient conditions of the synthesized ε-FeOOH phase (orthorhombic, P21nm) were listed in Table 1 when compared with ε-FeOOH synthesized in other laboratories [26]. We found the ambient lattice parameters of our sample were consistent with other studies, which confirmed the composition of the synthesized ε-FeOOH was fully hydrogenated.…”
Section: Methodssupporting
confidence: 87%
“…ε-FeOOH is thermodynamically stable in cold subducted slabs [25]. It is quenchable to ambient conditions once the crystal is synthesized in a multi-anvil press [26,27]. We followed the recipe by Suzuki [26,27] by compacting goethite powder in a gold capsule, rolling in a rhenium heater, and placing it in a Kawai-type multi-anvil press at the Geophysical Laboratory, Carnegie Institution of Washington.…”
Section: Methodsmentioning
confidence: 99%